DEVELOPING URBAN WALKABILITY MEASURES GROUNDED IN GREEN URBANISM PRINCIPLES USING THE DELPHI SURVEY STUDY - Ayob, Zulkefle; Amir, Atikah Raihanah (PLANNING MALAYSIA, 2024)
This paper investigates the correlation between Green Urbanism Principles (GUP) and urban walkability. It begins with a Literature Investigation to identify green urbanism components and principles by utilising the Green Urbanism concept by Beatley and Lehmann's Principles of Green Urbanism as a framework. Three-stage Delphi Surveys were conducted to conclude the associated GUP, parameters, potential indicators, and themes of Green Urbanism Quality with urban walkability. The study addresses a literature gap, which is found by linking green urbanism principles to walkability indices and fills it effectively. The outcome is the validated Green Urbanism Walkability Index (GUWI). Moreover, the research emphasises the need for a quality urban environment that stimulates walking in Malaysia. Four main themes of Green Urbanism Quality, namely Nature, Urbanism, Liveability, and Culture and Identity, significantly promote urban walkability. A walkable city triggers positive effects, including lively street-level activities, increased security, and economic stability. Landscapes, greeneries, and well-integrated pedestrian networks further enhance walkability. The results emphasise the crucial link between green urbanism principles and the walkability index, allowing for better identification and measurement of walkability. Implementing the system requires enhancing technical and cultural aspects through training, education, and regulation. This research contributes significantly to the body of walkability studies, particularly in the Malaysian context.